COVID-19 and chronic fatigue syndrome: Is the worst yet to come?. (January 2021) - Wostyn, Peter
Abstract: There has been concern about possible long-term sequelae resembling myalgic encephalomyelitis/chronic fatigue syndrome in COVID-19 patients. Clarifying the mechanisms underlying such a "post-COVID-19 fatigue syndrome" is essential for the development of preventive and early treatment methods for this syndrome. In the present paper, by integrating insights pertaining to the glymphatic system and the nasal cerebrospinal fluid outflow pathway with findings in patients with chronic fatigue syndrome, idiopathic intracranial hypertension, and COVID-19, I provide a coherent conceptual framework for understanding the pathophysiology of post-COVID-19 fatigue syndrome. According to this hypothesis, this syndrome may result from damage to olfactory sensory neurons, causing reduced outflow of cerebrospinal fluid through the cribriform plate, and further leading to congestion of the glymphatic system with subsequent toxic build-up within the central nervous system. I further postulate that patients with post-COVID-19 fatigue syndrome may benefit from cerebrospinal fluid drainage by restoring glymphatic transport and waste removal from the brain. Obviously, further research is required to provide further evidence for the presence of this post-viral syndrome, and to provide additional insight regarding the relative contribution of the glymphatic-lymphatic system to it. Other mechanisms may also be involved. If confirmed, the glymphatic-lymphatic system could represent a target in combating post-COVID-19 fatigue syndrome. Moreover, further research in this area could also provide new insights into the understanding of chronic fatigue syndrome.